Dating tectonic activity in the Lepontine Dome and Rhone-Simplon Fault regions through hydrothermal monazite-(Ce) - Bergemann, Christian A. (Solid earth, 2020)
Abstract. Zoned hydrothermal monazite-(Ce) from Alpine-type fissures and clefts is used to gain new insights into the tectonic history of the Lepontine Dome in the Central Alps and the timing of deformation along the Rhone-Simplon Fault zone on the dome's western end. Hydrothermal monazites-(Ce) (re)crystallization ages directly date deformation that induces changes in physicochemical conditions of the fissure or cleft fluid. A total of 480 secondary ion mass spectrometry (SIMS) spot analyses from 20 individual crystals, including co-type material of the monazite-(Nd) type locality, record ages for the time of ∼19 to 2.7 Ma, with individual grains recording age ranges of 2 to 7.5 Myr. The combination of these age data with geometric considerations and spatial distribution across the Lepontine region gives a more precise young exhumation history for the area. At the northeastern and southwestern edges of the Lepontine Dome, units underwent hydrothermal monazite-(Ce) growth at 19-12.5 and 16.5-10.5 Ma, respectively, while crystallization of monazite-(Ce) in the eastern Lepontine Dome started later, at 15-10 Ma. Fissure monazite-(Ce) along the western limit of the dome reports younger ages of 13-7 Ma. A younger age group around 8-5 Ma is limited to fissures and clefts associated with the Simplon normal fault and related strike-slip faults such as the Rhone Fault. The data set shows that the monazite-(Ce) age record directly links the fluid-induced interaction between fissure mineral and host rock to the Lepontine Dome's evolution in space and time. A comparison between hydrothermal monazite-(Ce) and thermochronometric data suggest that hydrothermal monazite-(Ce) dating may allow us to identify areas of slow exhumation or cooling rates during ongoing tectonic activity.
Gesehen am 31.03.2020